THE AVIATION-RELATED COMPONENT THAT COMPRISES THE SCOPE OF URBAN NAMES IN KYIV AND ITS USE IN COMMEMORATIVE PRACTICES - Agieieva, Galyna (Theory and practice of design, 2024)
The paper examines urban planning situations, processes of formation and transformation of systems of urban names, their effect on the formation of historical memory and the possibility of use in commemorative practices. The purpose of the paper is to research the processes and results of the transformation of the system of urban names of Kyiv, and their effect on urban planning situations, in particular, the creation of «memorial places». Object of study is a component of the system of urban names related to aviation, rocketry, and cosmonautics. The choice of chronological boundaries, which are 2017–2023, is connected, first of all, with the availability of quantitative indicators of aviation-related urban names obtained during research carried out by experts of the Department of Urban Planning in 2017. The year is the lower threshold of the chronological limit of this study. The year 2023 is adopted as the upper threshold, when active discussion of proposals for renaming Povitroflotskyi Avenue were under way. Research methodology is based on the use of the methods that include the study of cartographic materials; processing information about the history of names granted, restored and changed; comparative and critical analysis; a systematic approach to the study of the object as a component of the urban environment and its effect on the social environment. The results. The data that form the scope of urban names of the city were analyzed. The urban names related to aviation, rocketry and cosmonautics (aviation- related urban names) were outlined, with their types determined (names of streets, alleys, avenues, squares, pocket parks. Quantitative indicators of their importance in the system of urban names of the city and type-related subsystems were evaluated. All aviation-related urban names (30) are found to belong to the memorial category. Most of them are located in the Sviatoshynskyi and Solomyanskyi administrative districts of the city that pertain to aviation enterprises, research and cultural and educational institutions, and institutions of higher education. The results of the implementation of de-russification and de-communization measures were analyzed, in particular, the updating of the toponymic map of Kyiv during the period under study. Quantitative indicators of the changing of aviation-related urban names (13), restoration (2) and the granting of new names (11), including memorial ones (6), which perpetuate the names of famous persons and events related to the exploration of space and the development of aviation, were revealed. Scientific novelty. Based on a systematic approach to the study of urban planning situations and the scope of urban names in Kyiv, the possibility of strengthening the effect of aviation-related urban names on the social environment of the area of attraction objects by means of other types of commemorative practices is assessed. Practical significance. The obtained results can be used to form accomplished «places of memory» based on the objects to which they pertain, using material, visual, and other means, and areas of influence on the social environment so that commemorative practices can be further implemented.